2019
DOI: 10.37510/godzbo1972169k
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis of the short version of attitudes toward lesbians and gay men scale (ATLG-S)

Abstract: This study aims to examine the psychometric properties of the short version of Attitudes Toward Lesbians and Gay Men Scale (ATLG) translated in Macedonian language. A total of 500 undergraduate students who study 5 different disciplenes (Medicine, Stomatology, Psychology, Special education and rehabilitation and Social work) participated voluntarily by providing answers to several questionnaires: the target instrument (ATLG-S) Transphobia Scale (TS)), Eight Item Empathy Quotient test, the short version of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Based on the item analysis of the 20 items, six items (Item 2, 4, 7, 9, 17, and 19) were removed from the original scale resulting in a short 14-item scale. EFA supported the existence of two factors (ATL and ATG), as was theoretically expected ( Herek, 1988 ; Yu et al, 2011 ; Kenig, 2019 ): six items measuring ATL and eight items related to ATG. CFA results indicated that the two-factor model fit the data better than the one-factor model.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Based on the item analysis of the 20 items, six items (Item 2, 4, 7, 9, 17, and 19) were removed from the original scale resulting in a short 14-item scale. EFA supported the existence of two factors (ATL and ATG), as was theoretically expected ( Herek, 1988 ; Yu et al, 2011 ; Kenig, 2019 ): six items measuring ATL and eight items related to ATG. CFA results indicated that the two-factor model fit the data better than the one-factor model.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, Moreno et al (2015) found that the omission of item 4 (“Female homosexuality in itself is no problem, but what society makes of it can be a problem”) yielded in increase in Cronbach’s α. More importantly, Herek and McLemore (2011) recommended to use the shorter versions instead of the original version, because these short versions were highly correlated with the original version, and in recent years the shorter versions (e.g., the five- item versions of the ATL and ATG scale) have been used more and more frequently ( Herek and Gonzalez-Rivera, 2006 ; Song et al, 2013 ; Zhang et al, 2016 ; Kenig, 2019 ).…”
Section: Discussionmentioning
confidence: 99%